(untitled) (International Journal of Physiotherapy, 2017)
Background: It is well known that Iliotibial band syndrome (ITBS) is the most frequent overuse injury in recreational runners. Given the fact that there are no clear guidelines on the optimal conservative treatment approach regarding ITBS rehabilitation, manual therapy effect by a functional joint mobilization is still unknown. The purpose of the study was to investigate whether implementation of mobilization-with-movement (MWM) and auto-mobilization had a significant short-term improvement in pain and functionality of recreational runners with ITBS. Methods: Participants: thirty ITBS patients, were randomly assigned into two groups. Design and Settings: One group pre-test /post-test with the control group. Interventions: Runners on the treatment group followed an MWM protocol of six sessions with an additive program of auto-MWM, while the control group received a SHAM form of MWM. Outcome measurements: Pain and functionality were measured at baseline and post-treatment, via Numeric Pain Rating scale and Lower Extremity Functional Scale respectively. Mixed-ANOVA test detected possible differences among treatment phases and between groups, but also interactions among factors. Result: The present findings revealed significant interactions between factors and significant main effects of each TIME and GROUP factors on pain and functionality. MWM-treatment group showed significant improvement in post-intervention NPRT and LEFS scores, compared to baseline scores (p<.001). SHAM-MWM group exhibited no significant differences on post-NPRT and LEFS scores, compared to baseline (p>.001). Differences between groups were significant in post-treatment scores (p<.001). Conclusion: Our findings suggest that MWM and auto-MWM are a significant treatment approach, improving pain and functionality in recreational runners suffering from ITBS.